Concentrations and health risk assessment of rare earth elements in vegetables from mining area in Shandong, China. (February 2017) - Zhuang, Maoqiang; Zhao, Jinshan; Li, Suyun; Liu, Danru; Wang, Kebo; Xiao, Peirui; Yu, Lianlong; Jiang, Ying; Song, Jian; Zhou, Jingyang; Wang, Liansen; Chu, Zunhua
Abstract: To investigate the concentrations of rare earth elements in vegetables and assess human health risk through vegetable consumption, a total of 301 vegetable samples were collected from mining area and control area in Shandong, China. The contents of 14 rare earth elements were determined by Inductively Coupled Plasma—Mass Spectrometry (ICP—MS). The total rare earth elements in vegetables from mining and control areas were 94.08 μg kg −1 and 38.67 μg kg −1, respectively, and the difference was statistically significant (p < 0.05). The leaf vegetable had the highest rare earth elements concentration (984.24 μg kg −1 and 81.24 μg kg −1 for mining and control areas, respectively) and gourd vegetable had the lowest rare earth elements concentration (37.34 μg kg −1 and 24.63 μg kg −1 for mining and control areas, respectively). For both areas, the rare earth elements concentration in vegetables declined in the order of leaf vegetable > taproot vegetable > alliaceous vegetable > gourd vegetable. The rare earth elements distribution patterns for both areas were characterized by enrichment of light rare earth elements. The health risk assessment demonstrated that the estimated daily intakes (0.69 μg kg −1 d −1 and 0.28 μg kg −1 d −1 for mining and control areas, respectively) of rare earth elements through vegetable consumption were significantly lower than the acceptable daily intake (70 μg kg −1 d −1 ). The damage to adults can be neglected, but more attention should be paid to the effects of continuous exposure to low levels of rare earth elements on children. Highlights: REE concentration in vegetables of mining area was significant higher than that of control area. REE concentration declined in the order of leaf vegetable > taproot vegetable > alliaceous vegetable > gourd vegetable. Total REE was dominated by light rare earth elements. More attention should be paid to the effects of continuous exposure to low levels of REE on children.